-6+3y=-27

Simple and best practice solution for -6+3y=-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+3y=-27 equation:



-6+3y=-27
We move all terms to the left:
-6+3y-(-27)=0
We add all the numbers together, and all the variables
3y+21=0
We move all terms containing y to the left, all other terms to the right
3y=-21
y=-21/3
y=-7

See similar equations:

| (20-3x)/x=2x | | 3x-33+10x=180 | | x.x^2+2x-35=0 | | (x)+(x+1)+(x+2)=93 | | -13.9+1.5v=-17.35 | | -34=-41+t/7 | | -24=2v-6 | | 4x-36=20x-12 | | -30=7z-51 | | -9=-2y+7(y+3) | | 4y+-9=-37 | | 3x=+918 | | (5-x/x)=0.06 | | -6u+3(u-3)=18 | | 5-x=0.06x | | 8x÷15=24 | | 4/x+0.75=2/x-4 | | 98m^2=18 | | (X-6)-(3x+2)=4(2x+2) | | 16h^2+8=-12 | | 5^x=5^{3x-2} | | 9(4x-8)-(x+3)=(x+9)5 | | 5x+3=-x-7+4x | | 11^(6x+2)=12 | | 4x(2)-64=0 | | 6y+4=4.4 | | 4x(×+3)=12 | | y=15000(1.04)^25 | | y=15000(1.04)²⁵ | | y/5-11=24 | | u/3+14=25 | | 9x+10=-5x+158 |

Equations solver categories